The Effects of ARCS Motivational Instruction in Physical Education on Learning Cognition and the Health-Related Physical Fitness of Students - Luo, Xi; Liu, Liu; Li, Jingjing (Frontiers in Psychology, 2022)
The change in lifestyles, and the effect of academic pressure result in students largely reducing the opportunity and time for outdoor activity. Besides, the increase in static lifestyles and the lack of physical activity have seriously threatened students’ health to result in obvious reducing health related physical fitness of domestic students (Kato et al., 2021). The problem should be emphasized and solved. To cultivate people’s exercise habits, it should be rooted downwards from childhood. Physical education in schools is the major channel to cultivate students’ development of a wholesome body and mind. Students with high flexibility, strong learning ability, and exercise experience in schools would deeply affect the future physical and mental development, the establishment of exercise concept, the formation of exercise habit, and the cultivation of motor skills.University students in Sichuan Province, as the research samples, are distributed 500 copies of questionnaire in this study. After deducting invalid and incomplete ones, 375 copies are valid, with the valid retrieval rate 75%. The research results conclude significantly positive correlations between 1. ARCS motivation instruction in physical education and learning cognition, 2. learning cognition and health related physical fitness, and 3. ARCS motivation instruction in physical education and health related physical fitness. According to the results to propose discussions, it is expected to have students acquire successful experience in exercise, build students’ self-confidence, increase students’ motivation to participate in physical activity, enhance students’ health related physical fitness, and cultivate students’ habits to engage in lifelong physical activity.